1992
DOI: 10.1063/1.106892
|View full text |Cite
|
Sign up to set email alerts
|

Insitu scanning tunneling microscopy observation of surface morphology of GaAs(001) grown by molecular beam epitaxy

Abstract: The surface morphology of molecular-beam-epitaxy-grown GaAs(001) has been investigated using in situ scanning tunneling microscopy and reflection high-energy electron diffraction. Films grown on nominally flat substrates at very slow growth rates display a multilevel system of terraces elongated along [11̄0], suggesting an edge energy anisotropy of the order of 10:1 and a preference for sticking at B-type steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(47 citation statements)
references
References 17 publications
2
44
0
1
Order By: Relevance
“…Numerous other in situ STM and diffraction studies appeared that all confirmed the presence of structures consistent with the missing-dimer models [61,[123][124][125][126][127]54,[128][129][130][131][132][133][134][135]. However, there was discrepancy in the reports for which of the four missing-dimer models was actually observed.…”
Section: ð2 â 4þ=cð2 â 8þmentioning
confidence: 83%
“…Numerous other in situ STM and diffraction studies appeared that all confirmed the presence of structures consistent with the missing-dimer models [61,[123][124][125][126][127]54,[128][129][130][131][132][133][134][135]. However, there was discrepancy in the reports for which of the four missing-dimer models was actually observed.…”
Section: ð2 â 4þ=cð2 â 8þmentioning
confidence: 83%
“…Consequently, a large build up of material occurs at the intersection between the (1 0 0) top plane and the (3 1 1)B facet and this region will contain a high density of B-type step edges. Since B-type step edges have a higher sticking probability for adatoms than A-type step edges [16] the profile of the (1 0 0) top plane is more peaked at the facet/(1 0 0) top plane intersection on these mesas than on mesas in the ½0 11 direction. A large dot density, (1.370.2) Â 10 11 cm À2 is seen in this peaked region (Fig.…”
Section: Mesa Stripe Oriented In the [0 1 1] Directionmentioning
confidence: 96%
“…18 -22 It is found that atomic segregation always leads to wider alloy regions at AlAs-onGaAs interfaces as compared to GaAs-on-AlAs interfaces, and the AlAs-on-GaAs interfaces also exhibit anisotropic inplane structures or anisotropic interface defects elongated along ͓1 គ 10͔, 19,20 which are probably related to step energy anisotropy on the reconstructed GaAs surface. 23,24 We believe that both effects can occur in the GaAs/Al x Ga 1Ϫx As system and contribute to the observed optical anisotropy.…”
Section: Optical Anisotropy Induced By Interface Asymmetrymentioning
confidence: 99%